1993
DOI: 10.1079/pns19930033
|View full text |Cite
|
Sign up to set email alerts
|

Chronic undernutrition in pregnancy and lactation

Abstract: Based on the dietary energy supply per person per d and a minimum energy requirement of 1.4 X basal metabolic rate (BMR), it is estimated that 11-32% of adults in developing countries were undernourished (Food and Agriculture Organization, 1990). Even if adequate amounts of food are available, unequal food distribution favouring men over women and cultural taboos may restrict food intake of women. Since they are usually engaged in productive activities which entail a substantial energy expenditure (McGuire & P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…Most results from studies conducted in less affluent societies have shown higher dietary intakes among lactating women than among pregnant or NP=NL women (Prentice et al, 1981;Guillermo-Tuazon et al, 1992;Kusin et al, 1993;Martínez et al, 1994;Piers et al, 1995), although a few studies failed to do so (Schutz et al, 1980;Adair, 1992). Among Filipino women, higher energy intake during lactation was associated with higher maternal postpartum weight (Adair & Popkin, 1992).…”
Section: Dietary Intake Exercise and Illnessmentioning
confidence: 94%
See 1 more Smart Citation
“…Most results from studies conducted in less affluent societies have shown higher dietary intakes among lactating women than among pregnant or NP=NL women (Prentice et al, 1981;Guillermo-Tuazon et al, 1992;Kusin et al, 1993;Martínez et al, 1994;Piers et al, 1995), although a few studies failed to do so (Schutz et al, 1980;Adair, 1992). Among Filipino women, higher energy intake during lactation was associated with higher maternal postpartum weight (Adair & Popkin, 1992).…”
Section: Dietary Intake Exercise and Illnessmentioning
confidence: 94%
“…A few investigators have found no difference or lower levels of physical activity during lactation (Tuazon et al, 1987;Singh et al, 1989;Kusin et al, 1993;Panter-Brick, 1993;Butte et al, 1997), whereas others have found higher levels during lactation (Armar- Klemesu & Wheeler, 1989;Madhavapeddi & Narasinga Rao, 1992). Among Filipino women (Adair & Popkin, 1992), higher energy expenditure was associated with greater risk of weight loss between 2 and 24 months postpartum.…”
Section: Dietary Intake Exercise and Illnessmentioning
confidence: 99%
“…Many adult females restrict their caloric and animal protein intake, thus further limiting protein intake (Prasad, 1996). Such dietary deficiency is known to cause detrimental effects on the outcomes of pregnancy in humans (GonzalezCossio and Delgado, 1991;Kustin et al, 1993) and laboratory animals (Zeman 1984;Pond et al, 1990;Snoeck et al, 1990). Protein deficiency during gestation enhanced the toxic effects of CO (Singh and MooreCheatum, 1993;, and mycotoxins (Singh andHood, 1985, 1987).…”
Section: Introductionmentioning
confidence: 95%
“…Protein deficiency and chronic malnutrition is widespread in the diets of poor pregnant women throughout the world (Kustin et al, 1993;Lupien, 1994). Many adult females restrict their caloric and animal protein intake, thus further limiting protein intake (Prasad, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Some genes are expressed fully during postnatal life when the intra-uterine influences will have disappeared. In chronic malnutrition throughout generations mothers may gain weight while their infants have a low birth weight (Kusin et al 1993). Proper growth-promoting factors such as insulin may be lacking in these infants.…”
Section: S D a H R I A N D Othersmentioning
confidence: 99%